(untitled) - Poppel, Harvey L. (New York, 1987)
What Megatrends did for business and society as a whole, this thought-provoking book does for the rapidly changing information technology industry. It shows what new products consumers can expect to see in the years ahead, which of the thousands of little-known companies in the industry today will emerge as the giants of tomorrow and how to take advantage of the opportunities the industry presents to those who fully understand it. Rather than just present isolated facts, the authors weave this information together to show the trends that are emerging and the sometimes revolutionary ways they are likely to affect industry and all of society for the remainder of this century. It includes comprehensive coverage of the five major segments of the industry: consumer electronics, communication services, information services, office equipment, and business operations equipment. For each segment, the book explains the challenges that firms will face in the coming years, the approaches most likely to succeed, and the products and services that are expected to result through the mid-1990s.
Keywords: Computer industry,Telecommunication equipment industry,Market surveys